ANALISIS PENGARUH ATRIBUT PRODUK TERHADAP KEPUTUSAN SISWA MEMILIH LEMBAGA KURSUS BAHASA INGGRIS BUDIWIJAYA CABANG PARAMESWARA PALEMBANG - Barlian Valention; Diah Natalisa; Welly Nailis (Jurusan Manajemen Fakultas Ekonomi Universitas Sriwijaya, 2012)
ABSTRACT This research was aimed at identifying the influence of a product′s attributes on the students’ decision to select Budiwijaya English Course, Parameswara Branch, Palembang and the most dominant attribute they chose. The data were collected by questionnaires, interview and library research, and analyzed by descriptive qualitative and quantitative techniques (linear multiple regression technique) using SPSS 12.00 for Windows. The results show that all attributes (brand, services, traits and quality) influenced the students’ decision to select Budiwijaya English Course, Parameswara Branch, Palembang and the most dominant one is services.